Multi Cycle and Material Deposition for Spatial Atomic Layer Deposition Process - Varga, Atilla C.; Carnoy, Matthias; Kundrata, Ivan; Plakhotnyuk, Maksym; Bachmann, Julien (2023 IEEE Nanotechnology Materials and Devices Conference, NMDC 2023, 2023)
Spatial Atomic Layer Deposition (sALD) offers a unique opportunity for localized deposition due to its physical separation and isolation of precursor and co-reagent dosing.[1] However, although simple in theory, due to well-developed examples of sALD, in practice miniaturization of sALD requires substantial effort into the creation of suitable micro-nozzles.[1] Uniquely, ATLANT 3D has developed proprietary sALD micronozzles, called microreactor Direct Atomic Layer Processing - μDALP™.
CRIS-Team Scopus Importer:2024-12-16